UTILIZATION OF LONTAR PALM (Borassus flabellifer) FRUIT PEEL WASTE INTO LIQUID ORGANIC FERTILIZER (POC) AS AN EFFORT TO REDUCE LOCAL ORGANIC WASTE IN CHARANG VILLAGE, PATTANI, THAILAND - Hasanah, Rafiatul; Fajrin, Chamelia Muclis; Fajar, Dinar Maftukh; Meah, Jekbaseeroh (Journal of Community Service, 2026)
This Community Service Program (PKM) was implemented to address the issue of organic waste in Charang Village, Yaring District, Pattani Province, Thailand specifically, waste from lontar palm (Borassus flabellifer) husks, which have long been considered worthless and simply discarded. This problem has led to waste accumulation, unpleasant odors, and environmental pollution. The proposed solution is to convert lontar fruit peels into liquid organic fertilizer (POC) through a simple fermentation process using the EM4 bioactivator and molasses. Activities included community outreach, semi-structured interviews, and hands-on fermentation training using the Asset-Based Community Development (ABCD) approach, which emphasizes the utilization of local assets and active community participation. The evaluation showed an increase in community knowledge and skills of approximately 80%, with farmer leaders committed to applying POC on their farmland and homemakers consistently processing household organic waste. A trial on water spinach demonstrated tangible success, with growth 2–4 cm faster than the control group, greener leaves, and sturdier stems. These results demonstrate that converting lontar waste into liquid organic fertilizer not only reduces organic waste generation but also supports sustainable agriculture, reduces dependence on chemical fertilizers, and strengthens community participation in maintaining village cleanliness.